LINGKUNGAN VEGETASI DULU DAN KINI DI SITUS KOBATUWA II, NUSA TENGGARA TIMUR - Vita Matori (Balai Arkeologi Bali, 2013)
Kobatuwa II site is located in the Soa Basin, at an altitude of 345 metres above sea level, surrounded by hills and volcanoes, i.e. to the North is Mount Weawavo, Mount Hill Rega, Nuke, and Mangu, South of there is the mountain Inerie and the mountain Logobada, on the West by Mount Meze (Wolo Meze), on the East by Mount Matataka, in the Southeast by Mount Abulobo astronomically, it lay in the 08 position 41 & 23.5 South latitude and longitude 121 05' & amp; 09,3